Effectiveness of group counseling with positive self-talk in reducing anxiety among pregnant women in Indonesia: A true experimental study - Marimbun Marimbun; Nurhaliza Nurhaliza; Wan Chalidaziah (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2025)
Pregnancy can present significant risks, particularly during the childbirth process, which often induces fear and anxiety in pregnant women. This study aims to evaluate the effectiveness of group counseling using the Positive Self-Talk technique in reducing anxiety among pregnant women. A true experimental pretest-posttest control group design was employed, with 20 participants divided into two groups: 10 pregnant women in the experimental group and 10 in the control group. Anxiety data were collected using the Perinatal Anxiety Screening Scale (PASS), adapted to measure anxiety in pregnant women. Pre-test and post-test results were analyzed using the Wilcoxon Signed Ranks Test via SPSS 20. The findings revealed a significant reduction in anxiety within the experimental group (Asymp. Sig. = 0.037), with the average anxiety score decreasing from 84.5 at pre-test to 50.8 at post-test, while the control group exhibited an increase in the average anxiety score from 85.7 to 91.4 (Asymp. Sig. = 0.0628). These results suggest that group counseling with the Positive Self-Talk technique is effective in reducing anxiety among pregnant women. This study provides valuable insights into psychological interventions aimed at alleviating anxiety in pregnant women, particularly in preparation for childbirth.